The given function : h(x) = 6 - x
We know that for any functions f(x) and g(x)
f*g (x)=f(x)\times g(x)
Therefore , h*h (x)=h(x)\times h(x)
h*h (x)=(6-x)(6-x)=(6-x)^2
h*h (x)=(6)^2-2(6)(x)+x^2 [ Using identity (a-b)^2=a^2+2ab+b^2 ]
h*h (x)=36-12(x)+x^2
\-------->\ h*h (x)=36-12(x)+x^2 Now, at x= 10 , we get
h*h (10)=36-12(10)+(10)^2
h*h (10)=36-120+100=36+100-120=136-120=16
Hence, the value of (h*h)(10) = 16
hoped it helped
Answer: x = 7 or x = -8
x² + x - 56 = 0
⇔ x² + 8x - 7x - 56 = 0
⇔ x(x + 8) - 7(x + 8) = 0
⇔ (x - 7)(x + 8) = 0
⇔ x - 7 = 0
or x + 8 = 0
⇔ x = 7 or x = -8
Step-by-step explanation:
I think the correct answer would be : (-8,3)
I hope this helps !
Answer:
p = -1
x=10
m < 7
Step-by-step explanation:
4(3p + 6 ) = 12
Distribute the 4
12p +24 = 12
Subtract 24 from each side
12p+24-24 = 12-24
12p = -12
Divide by 12
12p/12 = -12/12
p = -1
-5(x -4) = -30
Distribute the -5
-5x+20 = -30
Subtract 20 from each side
-5x+20-20 = -30-20
-5x=-50
Divide by -5
-5x/-5 = -50/-5
x=10
-3m + 15 > -6
Subtract 15 from each side
-3m + 15-15 > -6-15
-3m >-21
Divide by -3 remember to flip the inequality
-3m/-3 < -21/-3
m < 7